The universal and easy-to-use standard of voltage measurement for quantifying the performance of piezoelectric devices. (September 2017) - Su, Yewang; Li, Shuang; Huan, Yong; Li, Rui; Zhang, Zhaohui; Joe, Pauline; Dagdeviren, Canan
Abstract: The output voltage is a key parameter to quantify the performance of piezoelectric devices, particularly for energy harvesters and sensors. Our recent work (Su et al., 2015) reported that the measured output voltage depends on the inner resistance of voltmeter used. It is contrary to the established concept that the measured results should be independent of the instruments used. Similar measurements, however, widely exist in recent published literature, which is actually not suitable to quantify the performance of piezoelectric devices. This paper proposes a universal and easy-to-use standard for the voltage measurement of piezoelectric devices. The output voltage measurements of a micro-fabricated, flexible lead zirconate titanate (PZT) mechanical energy harvester by two voltmeters with a resistance of 10  M Ω and 55  G Ω, present significantly different output voltage values ( ∼ 0.2 V vs. ∼ 2.0 V), which provide strong evidence for the unusual conclusion. A universal and easy-to-use standard of voltage measurement for piezoelectric devices requires that the inner resistance of voltmeter must be larger than a critical value in terms of effective capacitor, loading frequency and accuracy requirement of measured voltage. This standard is developed to obtain the open-circuit resistance-independent voltage. A self-developed electronic system meeting the standard requirement was built and the universality of all the findings was further validated by a commercial piezoelectric device.